PENGETAHUAN DAN SIKAP IBU YANG MEMILIKI ANAK BALITA TENTANG PERTOLONGAN PERTAMA PADA LUKA BAKAR DI KELURAHAN KEMENANGAN TANI KECAMATAN MEDAN TUNTUNGAN - Amira Permata Sari Tarigan; Endang Susilawati; Afniwati; Septiani Waruwu (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Mothers' knowledge and attitudes in treating burns are inadequate. Burns, if not treated immediately, will quickly cause complications in children under five such as dehydration and scarring. Burns are one of the most common injuries in children and adults, and the 11th cause of death in children aged 1-9 years. This study aims to determine the knowledge and attitudes of mothers and toddlers regarding first aid for burns. This research was designed with a cross-sectional design, and examined 105 respondents obtained through total sampling technique. Research data was collected through questionnaires. Through research, the level of knowledge of respondents was found: in the good category it was 43 people (41.0%), in the fair category it was 29 people (27.6%), in the poor category it was 33 people (31.4%); and the level of attitude of the respondents is: in the good category it is 91 people (86.7%), and in the fair category it is 14 people (13.3%). Through the results of the research, it is known that the level of knowledge and attitudes of mothers is in the good category, but some mothers still have knowledge in the fair and poor categories. It is hoped that health workers provide counseling and education about first aid for burns, so that the public, especially mothers with toddlers, can treat burns to their children.